Isotopic ratios of nitrate in aerosol samples from Mt. Lulin, a high-altitude station in Central Taiwan. (April 2017) - Guha, Tania; Lin, C.T.; Bhattacharya, S.K.; Mahajan, A.S.; Ou-Yang, Chang-Feng; Lan, Yi-Ping; Hsu, S.C.; Liang, Mao-Chang
Abstract: The importance of Asian countries towards increase of atmospheric pollutants is being examined critically in recent times. In this context, we carried out analysis of nitrates separated from aerosol samples collected during 2010 from Mt. Lulin (NOAA code: LLN), Taiwan, located at an altitude of 2 862 m above sea level. Large temporal variations are seen in δ 15 N, δ 18 O and Δ 17 O values of the nitrate, with day-to-day variations comparable to the seasonal amplitude. The δ 15 N values of nitrate are found to be higher in spring months (March–April; −1±3‰) and lower in summer (June–September; −5±3‰). Similarly, the δ 18 O (69 ± 15‰ versus 32 ± 13‰) and Δ 17 O (23 ± 5‰ versus 12 ± 4‰) values are higher in spring and lower in summer. The lowest δ 18 O value observed was 10.8‰. The higher values of δ 15 N in spring could be attributed to enhanced contribution from fossil fuel combustions, especially burning of coal in nearby Asian countries like China, with the resultant pollutants being brought to the Lulin station by long-range transport. An alternative explanation is the isotopic exchange reaction between N2 O5 and HNO3 that elevates the δ 15 N value in nitrate. The oxygen isotope variability is explained by changes in contribution from two major pathways of nitrate formation from its precursor NO x molecules. During spring time, nitrate formation via the N2 O5 pathway is dominant, resulting in higher values of both δ 18 O and Δ 17 O. In contrast, during summer, formation involving HO2 /RO2 radicals becomes important, producing lower values of δ 18 O and Δ 17 O. A chemistry box model was used to study the nitrate formation pathways through oxidation of NO and NO2 via formation of NO2 and NO3 − /HNO3 . Both the model results and observations suggest that for the formation of NO2 from NO, the pathway via O3 is more active in spring, whereas in summer the pathway via HO2 /RO2 radicals predominates. For the subsequent formation of NO3 − and HNO3, the OH pathway is more active in summer than in spring. These suggestions are supported by a wind rose diagram and back trajectory analysis of air masses bringing the precursor NO x to the sampling site. Highlights: Temporal variation in δ 15 N, δ 18 O and Δ 17 O values of nitrate aerosols at Mt. Lulin. Low δ 15 N values of nitrate in summer indicate anthropogenic emissions from China. Summer-time low values of δ 18 O and Δ 17 O suggest a formation pathway via OH radical. In contrast, the formation via N2 O5 pathway is preferred in spring-time. The interpretation on formation pathways is supported by a chemistry box model.